Oral rehabilitation of patients after maxillectomy. A systematic review - dos Santos, D. M. [UNESP]; de Caxias, F. P. [UNESP]; Bitencourt, S. B. [UNESP]; Turcio, K. H. [UNESP]; Pesqueira, A. A. [UNESP]; Goiato, M. C. [UNESP] (Elsevier, 2018)
Patients who have maxillectomy can be rehabilitated with reconstructive surgery or obturator prostheses with or without osseointegratable implants. To identify studies on possible treatments in this group, we systematically searched the Scopus, Embase, PubMed/Medline, and Cochrane databases to collect data on patients’ characteristics, radiotherapy, and results related to speech, swallowing, mastication or diet, chewing, aesthetics, and quality of life. Of the 1376 papers found, six were included, and one other was included after an additional search of references. A total of 252 patients were included, and of them, 86 had reconstructive surgery, 91 were treated with obturator prostheses, 39 had reconstructive surgery or obturator prostheses associated with implants, and 36 had reconstruction plus an obturator prosthesis. Data on radiotherapy were incomplete. There is a lack of consensus about the indication for rehabilitation, as the treatment must be based on the individual characteristics of each patient.
Keywords: Maxillofacial prosthesis; Oral surgical procedures; Palatal obturators; Reconstructive surgical procedures; Rehabilitation